Assessment of EGNOS Tropospheric Correction Model - Penna, Nigel (2001)
Within the implementation of the European Geo-stationary Navigation Overlay System(EGNOS),a significant residual error in positioning is due to tropospheric delay effects. The EGNOS guidelines recommend that tropospheric delay is modelled using an empirical correction algorithm based on a receiver's height and estimates of meteorological parameters developed from average and seasonal variation data. However, such a simple average and seasonal variation model is unlikely to emulate temporal weather changes exactly. The potential errors involved in the application of the recommended algorithm and the consequent effects on the positioning errors, under typical UK weather conditions, are detailed in this paper. This was achieved by comparing tropospheric delays produced by the EGNOS model, with tropospheric delays estimated from high precision carrier phase GPS, over a one-year period for five UK stations. The RMS EGNOS model zenith tropospheric delay errors ranged from 4.0 to 4.7 cm, with maximum errors ranging from 13.2 to 17.8 cm. The errors were also shown to be spatially correlated. The subsequent effect on position error is shown to be dependent on the satellite elevation cut-off angle adopted and on whether or not the observations are weighted according to the satellite elevation angle.